The Effect of Mackerel Oil During Pregnancy on Apoptotic Index in the Cerebrum of Newborn Rattus Norvegicus - Madinah, Ali; Widjiati, Widjiati; Joewono, Hermanto Tri; Kholifah, Siti Nur; Latisfian, Mikra (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study is a true experiment with a posttest-only control group design. 30 pregnant Rattus norvegicus aged 2-3 months were randomly divided into 3 groups, namely the control group (K), the mackerel oil treatment group (P1), and the omega-3 supplements group (P2). The experimental animals were acclimatized and superovulated. The treatment was given at day 1-17 of pregnancy. 3 newborn Rattus norvegicus with the criteria of the largest, medium, and lightest body weight were taken from each parent to be made preparations on the 18th day. Examination of preparations carried out by immunohistochemistry. The mean ± SD of the apoptosis index in the cerebrum were 4.93 ± 0.87 (K), 2.53 ± 0.45 (P1), and 3.72 ± 0.54 (P2). The results of statistical tests showed that there was a significant effect on the apoptotic index in the cerebrum of newborn Rattus norvegicus between groups with p-value <0.05.